2017
DOI: 10.1016/j.ydbio.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive WNT/CTNNB1 activation triggers spermatogonial stem cell proliferation and germ cell depletion

Abstract: The differentiation of germ cells into oogonia or spermatogonia is the first step that eventually gives rise to fully mature gametes. In the female fetal gonad, the RSPO1/WNT/CTNNB1 signalling pathway is involved in primordial germ cell proliferation and differentiation into female germ cells, which are able to enter meiosis. In the postnatal testis, the WNT/CTNNB1 pathway also mediates proliferation of spermatogonial stem cells and progenitor cells. Here we show that forced activation of the WNT/CTNNB1 pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 60 publications
3
27
1
Order By: Relevance
“…In male gonads in mice, the RSPO1 protein can activate the WNT/CTNNB1 signalling pathway to enhance PGC specialisation (Chassot et al, 2011). Overexpression of the WNT/CTNNB1 signalling pathway could downregulate the specialisation of spermatogonia and cause spermatocyte apoptosis, ultimately resulting in testicular hypoplasia (Chassot et al, 2017). The predicted miRNA-mRNA/lncRNA interaction network based on overlapped DE miRNAs included important genes in the WNT pathway, showing that the WNT pathway plays an important role in regulating polyploid infertility, and further provides a direction for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In male gonads in mice, the RSPO1 protein can activate the WNT/CTNNB1 signalling pathway to enhance PGC specialisation (Chassot et al, 2011). Overexpression of the WNT/CTNNB1 signalling pathway could downregulate the specialisation of spermatogonia and cause spermatocyte apoptosis, ultimately resulting in testicular hypoplasia (Chassot et al, 2017). The predicted miRNA-mRNA/lncRNA interaction network based on overlapped DE miRNAs included important genes in the WNT pathway, showing that the WNT pathway plays an important role in regulating polyploid infertility, and further provides a direction for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…As spermatogenesis is a multifactorial complex process which requires the coordination of germ cells and testicular somatic cells [100], an in vitro model that maintains testis specific cell associations is essential. Studies have shown that testis specific architecture is required for germ cell homeostasis [90] and a number of paracrine factors, such as glial cell line-derived neurotropic factor, colony-stimulating factor 1 [101–105] and signalling molecules such as wnt6 and wnt3a released by somatic cells are required for germ cell maintenance [106, 107]. Thus, a testicular organoid model with testis specific architecture and function can serve as a bridge between 2D culture and animal models.…”
Section: Potential Applications In Male Reproductive Biology and Toximentioning
confidence: 99%
“…Another study indicated that Fgf2 may regulate SSCs proliferation in vitro via phosphorylation on Akt and Erk1/2 pathway (236). Finally, it should be mentioned that the activation of the Wnt/β-catenin pathway is thought to drive the transition from GfrÎą1 + to Ngn3 + spermatogonia, and signaling is likely initiated by Wnt6, which is uniquely expressed by Sertoli cells (222, 237, 238). Evidence for the importance of Sertoli cells as supporting/regulatory cells also comes from in vivo knockout experiments, which identified Sertoli cell specific genes, for example Connexin 43 (cx43), Swi-independent 3a (Sin3a), cytochrome P450 enzymes (Cyp26b1), and Ets related molecule (Erm), some of which play a role in the above pathways, that are essential in supporting germ cell proliferation and/or survival (239–242) and normal spermatogenesis (243).…”
Section: Testismentioning
confidence: 99%